Application of Digital Visual Storytelling on Kanji Character Acquisition: Effect on Learning Outcomes - Lensun, Sherly F; Bintang Pratiwi Harahap, Putri; Shirley Luntungan, Grace; Sambe, Nozomi (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This research aims to examine students' learning outcomes using the Digital Visual Storytelling on Kanji Character Acquisition model facilitated by Multimedia Presentations, and to assess the efficiency of this approach in enhancing students' proficiency in Japanese. This study's background indicates that numerous students struggle with learning Japanese due to pedagogical approaches that prioritize memory and are predominantly traditional in nature. This research employs a pre-experimental design utilizing an Intact-Group Comparison methodology. Data acquisition Observation and test administration (Pretest-Posttest). Statistical analysis: Descriptive and inferential statistics. This study demonstrates that the Digital Visual Storytelling on Kanji Character Acquisition learning approach utilizing Multimedia Presentations enhances Japanese language proficiency among students. The result is that the Digital Visual Storytelling on Kanji Character Acquisition paradigm utilizing Multimedia Presentations is demonstrably beneficial in enhancing students' Japanese language learning outcomes.